SOCIALIZATION OF ANALYSIS OF TOTAL TERPENOIDS FROM MANILTOA GRANDIFLORA (A. GRAY) SCHEFF LEAVES USING TLC METHODS - Jhon Patar Sinurat; Reh Malem br Karo; Rinaldo Berutu (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2021)
Saputangan leaves contained terpenoids which appeared reddish brown rings when tested using Liebermann Burchard, Salkowski and cerric sulfate. Saputangan leaves were macerated, then partitioned to obtain total terpenoids using a separatory funnel while checking filtrate partition with cerric sulfate. Extracts dissolved with methanol were partitioned with n-Hexane and then partitioned between aquadest and ethyl acetate in a ratio of 1: 1 to obtain 50 g of total terpenoids. TLC analyses was performed on total terpenoids using n-hexane: acetone (80:20 v/v) solvent. The total terpenoids were proved that terpenoids have 11 terpenoids as red stain based on their Rf. Based on the results of tests conducted on participants involved in socialization, it was stated that around 98% of participants had understood terpenoid compounds.